Inter-organizational supply chain performance: How the relationship factors influence the Australian beef industry? - Nasir Uddin, M.; Quaddus, Mohammed; Islam, Mohammad Nazrul (Reims Management School, 2011)
This study examines supply chain structures and inter-organizational relationship factors that influence the supply chain performance in the Australian beef industry. It investigated the extent to which aggregated relationship strength is a source of supply chain performance for the industry. The effect of antecedent factors such as vertical coordination, negotiation power and the use of IOS in the relationship strength were also investigated. Data were collected through a telephone survey in 315 firms including input suppliers, producers, processors and retailers in the beef industry of Western Australia and Queensland. The results support both the direction of theoretical underpinnings from RBV and TCE in the beef industry, that durable buyer-supplier relationships in the supply chain are developed from the level of commitment and trust, interdependence and mutual investment and can be a strategic economic resource to by-pass the cost of traditional market transactions. Results suggest the following key success factors for the beef industry in Australia: (a) the operational adoption of a lean supply chain between producer and processors or processors and retailers; (b) a transparent interdependent relationship with a strong consolidation/integration of business activities; and (c) synchronized information flows for greater compliance with carcass specifications in the supply chain.